KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT PADA BAYI - Yenny Aulya; Suprihatin Suprihatin; Siti Badriah Ahmad (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
Background: Based on WHO (Word Health Organization) report, Acute Respiratory Infection is still a major health problem in the world. This disease is a major cause of infectious disease morbidity and mortality worldwide. 59% of the visit rates at Zaenab Medika Clinic is Acute Respiratory Infection. Objective: This study aims to analyze the incidence of Acute Respiratory Infection among infants in Zaenab Medika Clinic district Bekasi.Methodology: This research is an analytic epidemiological study with a cross-sectional study design. The sample in this study were 88 infants. The sampling technique uses accidental sampling technique. The research instrument consisted of questionnaires, luxmeter, rollmeter, KMS. The questionnaire was tested for validity and reliability with a Cronbach's alpha coefficient of 0.972. Data were analyzed using univariate and bivariate analysis, the Chi-Square test to prove whether there was a relationship between variables.Results: The results of the bivariate analysis, it was that there was one independent variable related to the incidence of Acute Respiratory Infection in infants at the Zaenab Medika Clinic in Bekasi Regency, namely the physical environment of residence with a p value = 0.027. While the unrelated variables are maternal education, exclusive breastfeeding, and nutritional status.Conclusions: There is a Significant relationship between the physical environment of the residence and the incidence of Acute Respiratory Infection in infants. Suggestion Mothers who have babies with Acute Respiratory Infection are expected to pay more attention to the physical environment of the residence in accordance with the home health requirements of the Republic of Indonesia's Ministry of Health. Keywords: Physical environment of residence, maternal education, exclusive breastfeeding, nutritional status ABSTRAK Latar Belakang: Berdasarkan laporan WHO (Word Health Organization), Penyakit Infeksi Saluran Pernapasan Akut (ISPA) masih menjadi masalah kesehatan utama di dunia penyakit ini menjadi penyebab utama morbiditas dan mortalitas penyakit infeksi di seluruh dunia. Sebanyak 59% dari angka kunjungan di Klinik Zaenab Medika adalah penyakit ISPA.Tujuan: Penelitian ini bertujuan untuk menganalisis kejadian ISPA pada bayi di Klinik Zaenab Medika Kabupaten BekasiMetodologi: Penelitian ini merupakan penelitian epidemiologi analitik dengan desain studi cross-sectional. Sampel dalam penelitian ini berjumlah 88 bayi. Teknik pengambilan sampel menggunakan teknik accidental sampling. Instrumen penelitian terdiri dari kuesioner, luxmeter, rollmeter, KMS. Kuesioner telah diuji validitas dan reabilitas dengan nilai koefisien cronbach’s alpha 0,972. Data dianalisis menggunkan analisis univariat dan bivariat yaitu uji Chi-Square untuk membuktikan ada tidaknya hubungan antar variabel.Hasil Penelitian: Hasil analisis bivariat di ketahui bahwa terdapat satu variabel independen yang berhubungan dengan kejadian ISPA pada bayi di Klinik Zaenab Medika Kabupaten Bekasi, yaitu lingkungan fisik tempat tinggal dengan nilai p=0,027. Sedangkan variabel yang tidak berhubungan yaitu Pendidikan ibu, ASI ekslusif, dan Status gizi .Kesimpulan: Ada hubungan Signifikan antar Lingkungan fisik tempat tinggal dengan kejadian ISPA pada bayi. Saran Ibu yang memiliki bayi dengan ISPA di harapkan lebih memperhatikan Lingkungan fisik tempat tinggal sesuai dengan persyartan kesehatan rumah kementrian kesehatan republik indonesia. Kata kunci: Lingkungan fisik tempat tinggal, pendidikan ibu, ASI ekslusif, Status Gizi